2007
DOI: 10.1007/s00418-006-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic oxysterols induce caspase-independent myelin figure formation and caspase-dependent polar lipid accumulation

Abstract: Oxysterols, mainly those oxidized at the C7 position, induce a complex mode of cell death exhibiting some characteristics of apoptosis associated with a rapid induction of lipid rich multilamellar cytoplasmic structures (myelin figures) observed in various pathologies including atherosclerosis. The aim of this study was to determine the relationships between myelin figure formation, cell death, and lipid accumulation in various cell lines (U937, THP-1, MCF-7 [caspase-3 deficient], A7R5) treated either with oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 66 publications
2
26
1
Order By: Relevance
“…Moreover, it has been reported that 7-ketocholesterol can favor in vitro monocyte differentiation and foam cell formation (16). Interestingly, in the atherosclerotic process, the part played by unesterified cholesterol in intracellular lipid accumulation is well documented, and the associated cellular modifications, such as the presence of multilamellar cytoplasmic structures, recall the modifications observed under treatment with cytotoxic oxysterols (7-ketocholesterol, 7ß-hydroxycholesterol, cholesterol-5ß, 6ß epoxide) in various cell types (24,31,32,46): presence of multilamellar cytoplasmic structures (also called myelin figures) of various sizes and shapes (27) and intracellular accumulation of polar lipids revealed by Nile Red staining and subcellular fractionation associated with gaseous chromatography coupled with mass spectrometry (30,38). When the cells were treated with 7-ketocholesterol, these biochemical analyses also revealed an accumulation of cholesterol and 7-ketocholesterol in myelin figures.…”
Section: Cytotoxic Oxysterols: Powerful Inducers Of Phospholipidosismentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, it has been reported that 7-ketocholesterol can favor in vitro monocyte differentiation and foam cell formation (16). Interestingly, in the atherosclerotic process, the part played by unesterified cholesterol in intracellular lipid accumulation is well documented, and the associated cellular modifications, such as the presence of multilamellar cytoplasmic structures, recall the modifications observed under treatment with cytotoxic oxysterols (7-ketocholesterol, 7ß-hydroxycholesterol, cholesterol-5ß, 6ß epoxide) in various cell types (24,31,32,46): presence of multilamellar cytoplasmic structures (also called myelin figures) of various sizes and shapes (27) and intracellular accumulation of polar lipids revealed by Nile Red staining and subcellular fractionation associated with gaseous chromatography coupled with mass spectrometry (30,38). When the cells were treated with 7-ketocholesterol, these biochemical analyses also revealed an accumulation of cholesterol and 7-ketocholesterol in myelin figures.…”
Section: Cytotoxic Oxysterols: Powerful Inducers Of Phospholipidosismentioning
confidence: 91%
“…Whereas the involvement of an autophagic process is supported by the identification of LC3-II in 7-ketocholesterol-treated human aortic smooth muscle cells, the presence of cytoplasmic structures stained by the lysosome cationic lipophilic dye, monodansylcadaverine, which is detected before the loss of mitochondrial potential in 7-ketocholesterol-treated U937 cells, suggests instead that 7-ketocholesterol is a potent inducer of phospholipidosis (29). Indeed, under treatment with cytotoxic oxysterols, these structures, which are identified both in cells with condensed and/or fragmented nuclei characteristic of apoptotic cells and in cells with swollen nuclei considered as oncotic cells, can also be stained with Nile Red, which colors neutral and polar lipids yellow and orange/red, respectively (30). In addition, their biochemical characterization revealed that they contain a high concentration of phosphatidylcholine and sphingomyelin.…”
Section: Oxysterol-induced Cell Death and Associated Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations